Safety, Tolerability, and Pharmacokinetics of Multiple Repeated Oral Doses of the α2/3/5‐Subtype Selective GABAA‐Positive Allosteric Modulator PF‐06372865 in Healthy Volunteers. Issue 7 (19th January 2021) - Gurrell, Rachel; Whitlock, Mark; Wei, Hua; Shen, Zhongzhou; Ogden, Adam
Abstract: Multiple‐dose pharmacokinetics (PK) and safety were investigated in this phase 1 study of PF‐06372865, a positive allosteric modulator of α2/3/5 subunit‐containing γ‐aminobutyric acid A receptors (NCT03351751). In 2 cohorts (7‐8 PF‐06372865 and 2 placebo in each cohort), healthy adult subjects received twice‐daily oral doses of PF‐06372865 for 21 days, which included titration in the first 7 days, followed by a maintenance dose of 25 mg twice daily (Cohort 1) and 42.5 mg twice daily (Cohort 2) for 14 days. Serial PK samples were collected on days 1 and 21. Nineteen subjects were assigned to study treatments; 18 completed the study. Approximate dose‐proportional increases in maximum plasma concentratin and area under the plasma concentration–time curve over the dosing interval were observed. PF‐06372865 was rapidly absorbed with a median time to maximum concentration of 1 to 2 hours following both single‐ and multiple‐dose administration. Mean terminal elimination half‐life on day 21 was approximately 11 hours in both cohorts. All adverse events were mild; the most frequently reported was dizziness. After titration, there were no reports of somnolence. There were no clinically significant safety findings, including a lack of withdrawal symptoms on discontinuation of treatment. These results demonstrate that PF‐06372865 is safe and well tolerated at doses estimated to achieve high receptor occupancy (>80%), a profile differentiated from nonselective benzodiazepines.